2010
DOI: 10.1080/07315724.2010.10719895
|View full text |Cite
|
Sign up to set email alerts
|

Stressor States and the Cation Crossroads

Abstract: Neurohormonal activation involving the hypothalamic-pituitary-adrenal axis and adrenergic nervous and renin-angiotensin-aldosterone systems is integral to stressor state-mediated homeostatic responses. The levels of effector hormones, depending upon the degree of stress, orchestrate the concordant appearance of hypokalemia, ionized hypocalcemia and hypomagnesemia, hypozincemia, and hyposelenemia. Seemingly contradictory to homeostatic responses wherein the constancy of extracellular fluid would be preserved, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…[7] Genetic differences in magnesium utilization may account for differences in vulnerability to magnesium deficiency and differences in body responses to stress. [89] In our study, we found 76.47% patients of hypomagnesemia were on magnesium lowering drugs while as 46% of normomagnesemic patients were on magnesium lowering drugs. The difference was statistically significant ( P = 0.030).…”
Section: Discussionmentioning
confidence: 51%
“…[7] Genetic differences in magnesium utilization may account for differences in vulnerability to magnesium deficiency and differences in body responses to stress. [89] In our study, we found 76.47% patients of hypomagnesemia were on magnesium lowering drugs while as 46% of normomagnesemic patients were on magnesium lowering drugs. The difference was statistically significant ( P = 0.030).…”
Section: Discussionmentioning
confidence: 51%
“…Under conditions of acute stress, Se may be mobilized from SeMet-containing proteins in peripheral tissues and transported by selenoprotein P to the liver to facilitate increased biosynthesis of glutathione peroxidases. Glutathione peroxidases are then used to remove the increased amounts of reactive oxygen species produced during stress or to maintain redox status in cells (Weber et al, 2010). In support, in Chinook salmon that were transported by barge for 30 h, tissue Se concentrations of their frozen eviscerated carcasses decreased by 20% after the barge trip (Halver et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Because the intake of Mg is often inadequate and several other factors are also known to impair Mg supply (for example, diuretics use, diabetes mellitus, chronic alcohol consumption, stress factors) [16-18], more attention should in future be paid to possible consequences of insufficient or deficient Mg supply in the general population. Further studies on the interactions between Mg supply and vitamin D status should include a more detailed assessment of individual Mg status (for example, by measuring biochemical parameters of Mg status or by adjusting statistical analysis for stress factors, diuretics use, alcohol consumption and concomitant diagnoses such as diabetes); a more detailed investigation of different components of the vitamin D-parathyroid hormone axis in general populations; clarification of the dose?response relationship; and the realization of randomized controlled trials to verify whether oral Mg is indeed able to improve vitamin D status and survival.…”
Section: Resultsmentioning
confidence: 99%